Extremely Unusual Coronary Involvement in Cardiac Sarcoidosis - Amanpreet Singh Wasir; Manish Bansal; Anand Jaiswal; Surbhi Pande; Abha Thakur; Haimanti Sarin; Kartikeya Bhargava (Heart Views)
Left ventricular (LV) regional wall motion abnormalities are common in cardiac sarcoidosis but coronary occlusion is very rare. Here, we report a case of cardiac sarcoidosis with very unusual coronary involvement. A 43-year-old man presented with a persistent cough and a history of uveitis 6 months back with no other comorbidities. He was initially treated with empirical antitubercular treatment but continued to have an intractable cough and hence, underwent further evaluation. Echocardiography revealed global LV systolic dysfunction with inferior wall akinesia and LV ejection fraction 25%–30%. Cardiac magnetic resonance imaging confirmed these findings. It also showed subendocardial late gadolinium enhancement localized to the inferior wall segments with 50%–75% transmural extent. 18-fluorodeoxyglucose (FDG) positron emission tomography showed multiple FDG-avid lymph nodes all over the body along with intense myocardial FDG uptake confined to the inferior wall. Coronary angiography was performed which showed double-vessel disease with critical stenosis of the right coronary artery (RCA). Ultrasonography-guided fine-needle aspiration cytology from inguinal lymph nodes showed nonnecrotizing granulomas without any evidence of tuberculosis. He was started on steroids and appropriate heart failure medications and underwent percutaneous transluminal coronary angioplasty with stent to RCA. Later, he presented with hemodynamically stable ventricular tachycardia and received an implantable cardioverter defibrillator.